Differences : topographies of contemporary architecture - Solà-Morales Rubió, Ignasi, 1942-2001 (Writing architecture., 1997)
Differences brings together ten essays written over the past decade by the distinguished Spanish architect and theorist Ignasi de Solà-Morales.